Clinical management of heart failure with improved ejection fraction: treatment and maintenance - XU Tianyun; SHEN Yiming; JIANG Meng (Shanghai Jiaotong Daxue xuebao. Yixue ban)
In patients with heart failure with reduced ejection fraction (HFrEF), some individuals demonstrate significant improvement in left ventricular ejection fraction (LVEF) during subsequent evaluations after treatment. The 2022 American Heart Association/American College of Cardiology/Heart Failure Society of America (AHA/ACC/HFSA) heart failure management guidelines introduced the term "heart failure with improved ejection fraction (HFimpEF)" to describe patients with prior LVEF≤40% that subsequently increased above 40% during follow-up. Studies indicate that HFimpEF patients exhibit lower all-cause mortalities and heart failure rehospitalization rates, with a significantly better prognosis compared to HFrEF patients, establishing HFimpEF as a staged therapeutic target for HFrEF. Current discussion on HFimpEF primarily focuses on two aspects: characteristics of the target population and effective methods for LVEF improvement, and maintenance strategies for cardiac function preservation in HFimpEF patients; particularly the latter lacks clear clinical-guideline recommendations. Therefore, reviewing existing research to systematically summarize therapeutic strategies that promote the HFrEF-to-HFimpEF transition and effective maintenance approaches for HFimpEF becomes crucial. This article comprehensively reviews the LVEF-improving effects of current pharmacological, device-based, and surgical interventions, along with monitoring and management strategies for HFimpEF patients. In HFrEF patients, clinical evidence suggests that β-blockers and cardiac resynchronization therapy can significantly improve LVEF beyond 40%. Regarding HFimpEF management, sodium-glucose cotransporter-2 inhibitors (SGLT2i) and renin-angiotensin system inhibitors (RASi) demonstrate efficacy in maintaining LVEF and cardiac function. Additionally, this review identifies current research limitations in HFimpEF and proposes potential future research directions.